(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The purpose of the present study is to examine the major factors related to the participation of women in the economic activities of Bangladesh, using the data of the nationally representative provided by the Bangladesh Demographic and Health Survey (BDHS) 2017/18. The survey interviewed a total of 20127 women aged 15-49 on social, economic, and demographic factors. The study used women’s occupations as the dependent variable to understand the patterns and dynamics of women’s participation in economic activities in Bangladesh. The result shows that 49.6% of women didn’t associate with any work, 7.9% of women worked as a professional, technical or managerial specialist, and 42.5% of women worked as non-professional, such as: in agriculture, and domestic-related work. Two policy implications emerged from the study: 1) The economic activity of women in Bangladesh is still low, most of them earn their livelihood utilizing non-professional works; 2) Women who are relatively from poorer families, not very well educated, located in the rural area are largely seen in economic activities in Bangladesh. Finally, the study indicates an idea about important determinants of women’s employment, as poor women with little formal education remain economically active. The study recommends that women must be provided with new skills and knowledge to expand their ability and the education of women must be given the highest priority, which is the fundamental problem.